Penerapan Akuntansi Lingkungan Sebagai Bentuk Pertanggungjawaban Perusahaan Terhadap Lingkungan - Dyah Ayu Kumala Sari; Ersi Sisdianto (Akuntansi, 2024)
Today business sustainability does not only depend on financial profits; it also depends on how the company helps society and the environment. The Quadrangle Bottom Line (QBL) paradigm, which considers economic, social, environmental and spiritual aspects, encourages companies to incorporate environmental accounting into their business strategies. This paradigm encourages companies to integrate environmental accounting into their business strategies. Environmental accounting increases transparency and accountability for stakeholders and helps companies measure, manage and report environmental impacts. Environmental accounting has been proven to increase business accountability and operational efficiency, such as the use of environmentally friendly technology and waste management. However, limited human resources and lack of standards are obstacles to its implementation. Therefore, stricter regulations are needed to encourage environmental accounting. This should include comprehensive reporting rules and bonuses for businesses. To balance business growth with environmental preservation, environmental accounting is a strategic step.